2007
DOI: 10.1002/jms.1252
|View full text |Cite
|
Sign up to set email alerts
|

Low‐energy collision‐induced fragmentation of negative ions derived from ortho‐, meta‐, and para‐hydroxyphenyl carbaldehydes, ketones, and related compounds

Abstract: Collision-induced dissociation (CID) mass spectra of anions derived from several hydroxyphenyl carbaldehydes and ketones were recorded and mechanistically rationalized. For example, the spectrum of m/z 121 ion of deprotonated ortho-hydroxybenzaldehyde shows an intense peak at m/z 93 for a loss of carbon monoxide attributable to an ortho-effect mediated by a charge-directed heterolytic fragmentation mechanism. In contrast, the m/z 121 ion derived from meta and para isomers undergoes a charge-remote homolytic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…The CID experiments with 11 and 12 yielded comparable spectra as those observed in the ESI-ISD experiments. The results from the CID experiments agree well with those reported by Attygalle and coworkers [25].…”
Section: Substituted Phenolssupporting
confidence: 92%
See 1 more Smart Citation
“…The CID experiments with 11 and 12 yielded comparable spectra as those observed in the ESI-ISD experiments. The results from the CID experiments agree well with those reported by Attygalle and coworkers [25].…”
Section: Substituted Phenolssupporting
confidence: 92%
“…They observed that the deprotonated precursor molecules readily lost either the HCO radical (may be via two steps) or the RCO radical to produce the phenoxide radical anions at m/z 92. The proposed mechanisms were studied using isotope labeling experiments [25].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In practical terms, such appears to be extracted randomly from several available positions. 4 In our explorations on collision-induced fragmentation of low-molecular-weight anions, 5,6 we noted a site-specific double-hydrogen migration which enables unequivocal differentiation of ortho isomers of alkyloxybenzoic acids from those of meta and para isomers. Moreover, this unique fragmentation enables facile generation of gaseous enolate anions which are known to act as intermediates in photochemical smog cycles, combustion reactions and many organic syntheses of complex compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations reveal that collision-induced fragmentation spectra of evenelectron ions of substituted aromatic compounds also show peaks diagnostic of the ortho-substitution position [13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%